Factors Affecting The Learning Satisfaction Of Faculty Dharma Duta Students In Entrepreneurship Courses - Krisdayanthi, Astrid; Rai Kristina, Ni Made; Riska Wulandari, Putu (Jayapangus Press, 2024)
Learning satisfaction is a factor that cannot be ignored in the learning process. From the mass Covid-19 pandemic to the present, students learn with two systems, namely online learning and offline learning. Of course, these two things produce different learning satisfaction. This study aims to: 1) describe student learning satisfaction in the Entrepreneurship course in online learning; 2) describe student learning satisfaction in the Entrepreneurship course in offline learning and 3) analyze factors that affect student learning satisfaction in the entrepreneurship course. This research is classified as qualitative descriptive research. The population of this study is students of the Faculty of Dharma Duta class of 2021 and 2022. Samples were taken as many as 130 respondents using purposive sampling techniques. The research instrument is a learning satisfaction questionnaire consisting of 26 statements. The data is analyzed descriptively. The results of the study are as follows: 1) student learning satisfaction in online learning is classified as satisfied; 2) Student learning satisfaction in offline learning is classified as very satisfied and 3) Factors that affect student learning satisfaction are learning facilities, the quality of lecturers in teaching, learning interaction and assessment in learning.